Direct C-H sulfenylation of purines and deazapurines - Klečka, Martin; Pohl, Radek; Čejka, Jan; Hocek, Michal (Organic & biomolecular chemistry, 2013)
A general method for Cu-catalyzed C-H sulfenylation of purines, 7-deaza- and 9-deazapurines with aryl- or alkyldisulfides has been developed. In purines, the reaction occurs at position 8, in 7-deazapurines at position 7 and in 9-deazapurines at position 9, leading to new interesting arylsulfanyl derivatives of purine or deazapurine bases. The resulting 8-arylsulfanylpurines undergo Liebesking-Srogl coupling with arylstannanes or boronic acids, whereas the (arylsulfanyl)deazapurines are not reactive under these conditions.
Keywords: Crystallography, X-Ray; puriny; síra; měď; Sulfur; Copper; Purines; krystalografie rentgenová